The influence of antigen organization on B cell responsiveness. - Bachmann, M; Rohrer, U; Kündig, T; Bürki, K; Hengartner, H; Zinkernagel, R (1993)
The influence of antigen epitope density and order on B cell induction and antibody production was assessed with the glycoprotein of vesicular stomatitis virus serotype Indiana [VSV-G (IND)]. VSV-G (IND) can be found in a highly repetitive form the envelope of VSV-IND and in a poorly organized form on the surface of infected cells. In VSV-G (IND) transgenic mice, B cells were unresponsive to the poorly organized VSV-G (IND) present as self antigen but responded promptly to the same antigen presented in the highly organized form. Thus, antigen organization influences B cell tolerance.